Color ranges: a methodological approach (ModaPalavra e-periódico, 2020)
This paper propose a methodology for creating color rangesfrom the identification of the design steps. The proposalconsists of establishing the color range as a synthesis of therelation of variables that guide the selection ofcolors byobjective criteria. The methodology relies on the Baxterdecision funnel diagram and outlines 3 specific steps:branding, trends and theme-moodboarding. The steps arecontextualized in the phases of research and generation ofideas and detailed according to the practice of creating colorcharts for the development of products.
Keywords: fashion design; color ranges; design methodology